Western intellectual insights for Muslim policy makers on religion based economy - Malik, Mohammad Manzoor (International Association of Computer Science and Information Technology Press (IACSIT), 2015)
The subject of relationship between religion and economy raises many issues. It touches the originality of religion and economy and their nature of relationship including their independence and dependence. Western scholarship on the subject has useful insights for the Muslim policy makers on religion based economy. This research undertakes Marx and Weber’s thought on the subject and relates the issue with the current reality in industrialized countries such as Singapore. The findings show that Marx is a reductionist and Weber’s thesis highlights the independent role of religion in fostering economy although he remains pessimistic regarding its religiosity. The more plausible view is that though religion is an independent variable, yet there is interdependence between religion and economy. The economical modalities influence religious life in many ways. This challenge calls Muslim policy makers for a continuous intellectual effort in making creative contributions in making religion based economy possible